(untitled) (Bangladesh Journal of Agricultural Research, 2012)
A field experiment was conducted at the `Research Farm` of Regional Seed Production Office of Lal Teer Seed Limited, Dinajpur, Bangladesh during November 2008 to April 2009. The study was conducted to investigate the effect of bulb size and planting spacing on seed production of cultivar Taherpuri onion. Three bulb sizes [small (5±2g), medium (10±2g), and large (15±2g)] and four planting spacing [closest 25×15, closer 25×20, wider 30×15, and widest 30×20cm] was considered in this experiment. Number of flowering stalks, length of flowering stalks, number of umbels per plant, number seeded fruits, seed weight per umbel, 1000-seed weight and seed yield per hectare were measured to assess the onion seeds. The results revealed that the highest seed yield (776.67 kg) per hectare was obtained from the large bulb (15±2g) with the closest spacing of 25×15cm followed by small bulb size of same spacing. The maximum number of flowers per umbel (371.39), seed weight per umbel (0.80g) and 1000-seed weight (3.92g) were obtained from the largest bulb size (15±2g) with widest (30×20cm) planting spacing. Hence, large bulb size with closest plant spacing is suggested for onion seed production in northern part of Bangladesh. Bangladesh J. Agril. Res. 37(3): 405-414, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12084